KINERJA LEMBAGA KEUANGAN MIKRO AGRIBISNIS GABUNGAN KELOMPOK TANI DALAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN DI KABUPATEN BANTUL - , Yopi Saleh ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The objective of this research are: (1) to find out the performance of MFIA Gapoktan PUAP in Bantul, (2) to find out the performance efficiency of MFI - A Gapoktan PUAP in Bantul, and (3) to identify the factors that influence the performance efficiency of MFI-A Gapoktan PUAP in Bantul. The research was conducted at 65 MFI -A Gapoktan PUAP in Bantul. The research method approach to monitoring and evaluation scoring method for measuring the performance of MFI-A Gapoktan PUAP in Bantul. The analysis approach of DEA (Data Envelopment Analysis) using the assumption of constant return to scale (CCR) and variable return to scale (BCC) with output oriented are used to measure the efficiency score of each MFI-A were observed. Furthermore, this research using Ordinary Least Squares (OLS) regression analysis to analyze the factors that influence the performance efficiency of MFI-A Gapoktan PUAP in Bantul. The results showed that the performance of MFI-A Gapoktan PUAP in Bantul included in quite well category. Based on calculation of DEA-CRS, 19 MFI-A (29,23%) has been efficient, while DEA-VRS calculations are as many as 33 MFI-A (50,77%) efficient. Manager education, age of MFI-A, time of service, and the number of administrators has a significant influence on the efficiency of MFI-A, while the loan method and the financing system of MFI-A did not significantly influence the efficiency of MFI-A Gapoktan PUAP in Bantul.